In GaN Double Heterostructure (DH) Laser Diode Performance And Optimization. - Thahab, S M; Abu Hassan, H; Hassan, Z (2007)

(untitled)
The laser performances of the blue DH InGaN laser diode (LD) structures have been numerically investigated by using ISE TCAD software.